Influence of Polymorphisms in Gene SATB2 on Antipsychotics Response in Chinese Han Population - Du X; Wang Y; Zhang Q; Gao Y; Wang X; Zhao W; Hu X; Zhang Y; Xu Y; Chen B; Zhang J; Liu S; et al. (Neuropsychiatric Disease and Treatment, 2025)
Xinzhe Du,1,2,* Yukun Wang,1,* Qian Zhang,3,* Yao Gao,1,2 Xiao Wang,1,2 Wentao Zhao,1,2 Xiaodong Hu,1 Yu Zhang,4,5 Yong Xu,1,2 Bo Chen,6 Jihui Zhang,6 Sha Liu,1 Xinrong Li1 1Department of Psychiatry, the First Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 2Shanxi Key Laboratory of Artificial Intelligence Assisted Diagnosis and Treatment for Mental Disorder, First Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China; 3Department of Medical Psychology, Shanxi Province Mental Health Center/Taiyuan Psychiatric Hospital, Taiyuan, Shanxi Province, People’s Republic of China; 4Key Laboratory of Cellular Physiology (Shanxi Medical University), Ministry of Education, Taiyuan, People’s Republic of China; 5Department of Physiology, School of Basic Medical Sciences, Shanxi Medical University, Taiyuan, People’s Republic of China; 6Department of Psychiatry, Sinopharm North Hospital, Baotou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xinrong Li, Department of Psychiatry, The First Hospital of Shanxi Medical University, 85 Jiefang Road, Yingze District, Taiyuan City, Shanxi Province, People’s Republic of China, Email lixinrong1225@163.com Sha Liu, Department of Psychiatry, The First Hospital of Shanxi Medical University, 85 Jiefang Road, Yingze District, Taiyuan City, Shanxi Province, People’s Republic of China, Email liusha@sxmu.edu.cnBackground: Responses to antipsychotic drugs vary significantly among patients with schizophrenia. This study explored the correlation between rs1900327, rs7557687, rs733156, and rs6745135 in gene SATB2 and antipsychotics response in the Chinese Han population.Methods: This study included 228 patients with schizophrenia. The polymorphisms of SATB2 gene (rs1900327, rs7557687, rs733156, and rs6745135) in patients were measured using the KASP technique. During the study, patients received a single antipsychotic medication for a duration of eight weeks. The clinical efficacy was evaluated using the Positive and Negative Syndrome Scale (PANSS) scores. A patient with a decrease of at least 50% in the total PANSS score was categorized as a good responder, whereas those who did not meet this threshold were classified as poor responders.Results: Polymorphisms of rs1900327, rs7557687 and rs733156 were associated with the decrease in PANSS on week 8; however, this was no longer significant after Bonferroni correction (p > 0.05). Four SNP polymorphisms of SATB2 were associated with reduced general psychopathology scores at week 8. At week 4, only rs733156 was associated with negative symptom changes at the 4th week. Good responders and poor responders showed no significant difference in the distribution of alleles and genotypes of the four loci (p > 0.05). The haplotype frequencies of rs6745135, rs1900327, rs7557687, and rs733156 were not significantly different between the two groups (p > 0.05). No SNP was significantly associated with antipsychotic treatment response under any of the five genetic models (codominant, dominant, recessive, overdominant, or Log -additive; p > 0.05).Conclusion: The SATB2 gene polymorphisms were related to the effectiveness of antipsychotics in treating general psychopathological symptoms.Keywords: schizophrenia, SATB2, gene polymorphism, antipsychotics